A STUDY TO EVALUATE MENTAL HEALTH STATUS AND COPING STRATEGIES AMONG BREAST CANCER SURVIVORS - QURESHI, I; SAMAR , V; SHAH , F; KHOWAJA , S; BIBI , H; SARWAR , S; SYED , BM (Biological and Clinical Sciences Research Journal, 2024)
Breast cancer survivors often experience significant stress due to the physical, emotional, and social challenges associated with their diagnosis and treatment. Understanding their stress levels and the coping strategies they employ is critical for developing effective interventions to improve their psychological well-being. Objective: The objective of the study was to assess the level of stress experienced by breast cancer survivors and to assess the most used coping strategies among breast cancer survivors. Analytical Cross-sectional study design was used. Data was collected at a single time to analyze the relationship between variables. Data was collected by using a validated scale (PCL-S) for assessing post-traumatic stress and the BRIEF COPE Inventory, a validated scale for measuring coping strategies. The study conducted at NIMRA Hospital Jamshoro aimed to determine the stress and coping strategies of 191 breast cancer survivors. Data collected during the period of 1st June 2024 to 30 June 2024.Methods: Data was gathered through purposive sampling techniques, specifically selecting individuals who meet the inclusion criteria for the study. Well-validated tools were utilized for data collection. Results: The results showed that of the total respondents, 12.6% suffered from Minimal to Negligible Stress, 17.8% from Mild Stress, 16.8% from Moderate Stress, and 52.9% from Severe Stress. At different levels of stress, other coping mechanisms were used. For these, the average scores were 15.54 with an SD of 5.16, 23.10 for Emotion-Focused Coping, and 23.52 for Dysfunctional Coping. Total scores were 2969.00, 4412.00, and 4492.00. The most popular was Dysfunctional Coping, particularly among the stressed segment of people. Conclusion: As observed in this study, nearly two-thirds of the respondents experienced severe stress. The strategies most frequently used to handle or cope with their stress by these subjects were Dysfunctional Coping, Emotion-Focused Coping, and Problem-Focused Coping. The high use of dysfunctional coping may reflect a serious need for interventions that would change maladaptive ways of coping with stress and give particular and more appropriate strategies for better coping, specifically for those highly stressed individuals.